Drought affects the fate of non-structural carbohydrates in hinoki cypress. (12th October 2021) - Tsuji, Chiaki; Dannoura, Masako; Desalme, Dorine; Angeli, Nicolas; Takanashi, Satoru; Kominami, Yuji; Epron, Daniel
Abstract: Tree species that close stomata early in response to drought are likely to suffer from an imbalance between limited carbohydrate supply due to reduced photosynthesis and metabolic demand. Our objective was to clarify the dynamic responses of non-structural carbohydrates to drought in a water-saving species, the hinoki cypress ( Chamaecyparis obtusa Sieb. et Zucc.). To this end, we pulse-labeled young trees with 13 CO2 10 days after the beginning of the drought treatment. Trees were harvested 7 days later, early during drought progression, and 86 days later when they had suffered from a long and severe drought. The labeled carbon (C) was traced in phloem extract, in the organic matter and starch of all the organs, and in the soluble sugars (sucrose, glucose and fructose) of the most metabolically active organs (foliage, green branches and fine roots). No drought-related changes in labeled C partitioning between belowground and aboveground organs were observed. The C allocation between non-structural carbohydrates was altered early during drought progression: starch concentration was lower by half in the photosynthetic organs, while the concentration of almost all soluble sugars tended to increase. The preferential allocation of labeled C to glucose and fructose reflected an increased demand for soluble sugars for osmotic adjustment. After 3 months of a lethal drought, the concentrations of soluble sugars and starch were admittedly lower in drought-stressed trees than in the controls, but the pool of non-structural carbohydrates was far from completely depleted. However, the allocation to storage had been impaired by drought; photosynthesis and the sugar translocation rate had also been reduced by drought. Failure to maintain cell turgor through osmoregulation and to refill embolized xylem due to the depletion in soluble sugars in the roots could have resulted in tree mortality in hinoki cypress, though the total pool of carbohydrate was not completely depleted.